The financial development of Yugoslavia - GOLDSMITH, R.W. (PSL Quarterly Review, 2014)
Yugoslavia is of particular interest for the comparative study of financial structure and development as it is the only country to combine a substantial degree of central planning and the ownership of most of the means of production by the state with a true financial system. Yugoslavia thus provides a unique opportunity to observe the adaptation of a financial system to conditions which in many respects are quite different from those in the West and in much of the Third World. The author first sketches the changes in economic organisation since 1945 and summarises the features of the infrastructure of the Yugoslav economy. A review of the trends of money, prices and interest rates over the last quarter century is then provided as well as a description of the main types of financial institutions and instruments. A brief discussion of the method of financing the main sectors follows as well as an attempt at constructing a rough balance sheet of the economy for the years 1952, 1962 and 1972. JEL: G10, G20, N24